PEMBERDAYAAN IBU-IBU DAN REMAJA PUTRI DALAM PENINGKATAN PENDAPATAN EKONOMI KELUARGA MELALUI PEMBUATAN ANEKA KUE KUE WARUNG BERBAHAN DASAR BERAS KETAN DI DESA PAYA PEUNAGA KECAMATAN MEUREUBO KABUPATEN ACEH BARAT - Yayuk Eko Wahyuningsih; Ivon Jalil; Leli Putri Ansari; Nila Trisna; Sri Rosmiati Sani (Jurnal Pengabdian Agro and Marine Industry, 2021)
The use of glutinous rice can be distinguished for household consumption and for industrial purposes, the average consumption of glutinous rice in rural areas is higher than in urban areas. In rural areas, there are still many people who consume sticky rice, both for snacks and as a mixture of rice such as yellow rice or others.The training for aking various of sticky rice cakes carried out in Paya Peunaga Village, Meureubo District, West Aceh Regency, where most of the people live in the agricultural sector  and  trade.  This  training  is  intended  for housewives and young girls who are members of the PKK/Family Welfare Empowerment in Paya Peunaga Village. The method in this activity was the lecture and practice which was attended by 15 participants. The   impact for participants who take part in the training on making various stall cakes made from glutinous rice, is expected to be able to make various stall cakes made from glutinous rice, especially for families at home as various variations of processed foods from glutinous rice. In addition, the final output is expected to make these various cakes and deposit them in food stalls, schools or cake shops and even supermarkets so that they can increase family income. KEYWORDS      Empowerment, housewives & young girls,    income and glutinous rice.